Geochemical and isotopic constraints on the source regions of phanerozoic carbonatites and associated alkaline rocks from the Zandkopsdrift complex of Namaqualand, South Africa, and the Marinkas Quellen, and Dicker Willem complexes in Namibia - Ogungbuyi, Ibiyemi Prisca (Department of Geological Sciences, 2020)
This is a study of Phanerozoic carbonatites and related alkaline silicate rocks from Zandkopsdrift in Namaqualand, South Africa (55 Ma), and Marinkas Quellen (529 Ma), and Dicker Willem (49 Ma) in southern Namibia, all emplaced within the Proterozoic Namaqua Natal province. The aims of this thesis are to characterise their mantle source region, including the timing and nature of the metasomatism that affected their sources, and to constrain their petrogenesis, particularly the relationships between the carbonatites and associated silicate igneous rocks. These associated silicate igneous rocks include olivine melilitite, aillikite and alkaline lamrophyre at Zandkopsdrift, nepheline syenite and trachyte at Marinkas Quellen, and ijolite and trachyte at Dicker Willem. At both Marinkas Quellen and Dicker Willem, the trachytes appear to be derived primarily from fenitised country rock. The major and trace element characteristics, enrichment in LREE and other incompatible elements, large Zr-Hf-Ti depletions and high Zr/Hf ratios all appear to have been inherited from a metasomatised mantle source region rather than being the result of residual source mineralogy. The δ18O and δ13C values of carbonate in the study locations vary significantly. The δ13C values (-3.9 to -8.8 ‰) are within the range of mantlederived carbonatites, whereas the δ18O values are often significantly higher (+8.64 to +22.22 ‰, versus SMOW) for “mantle-derived” carbonatites. The higher δ18O values observed are most likely attributable to low-temperature, post-emplacement alteration by hydrous fluids. O-isotope thermometry of the silicate mineral pairs (clinopyroxene, amphibole, and biotite) gives close to magmatic temperatures (≈800 oC), whereas the equilibration temperature of calcite-silicate mineral pairs is lower. The carbonatite and associated igneous rock samples contain unradiogenic Sr and mildly radiogenic Nd isotope compositions below and above Bulk Earth/CHUR values respectively. This suggests that carbonatite magmas were generated from sources with long-lived Rb/Sr lower than, and Sm/Nd higher than, the primitive mantle. In ƐHf(t)-ƐNd(t) space, the carbonatites and associated silicate rocks plot as much as 8 ƐHf units below the terrestrial ƐNd-ƐHf array, indicating mixing of a source with moderate ƐNd and exceptionally unradiogenic Hf isotope compositions. The radiogenic Pb isotope composition of the carbonatites (206Pb/204Pbi ratios from 18.06 to 22.38), is consistent with a source having high U/Pb, akin to the HIMU mantle end member. The radiogenic isotopes of the carbonatites and the alkaline silicate rocks seem most consistent with a dominantly asthenospheric source, with minor contributions from lithospheric sources. There is little evidence supporting the derivation of carbonatites at the three complexes from parental hybrid carbonate-silicate magmas. Rather, the evidence seems most consistent with deriving the carbonatites directly from very low-degree mantle melts, which subsequently become variably differentiated, first by melt-rock interaction in the mantle and subsequently by fractional crystallization. The associated silica undersaturated silicate igneous rocks appear most likely to represent relatively primitive (melilitites) to differentiated (nepheline syenites) melts of metasomatic wehrlites that were formed by carbonatite-peridotite melt-rock interaction.